Verapamil in patients with cluster headache with concurrent migraine - Robyn-Jenia Wilcha; Peter J. Goadsby (Cephalalgia Reports, 2024)
Background Verapamil is recommended as a first-line preventive for episodic and chronic cluster headache, however, its use is limited by a wide range of adverse events. From clinical practice at a tertiary headache centre, we have observed that the initiation of verapamil may be associated with headache worsening. The aim of this service evaluation was to examine whether verapamil initiation was associated with headache worsening, and whether these exacerbations may be attributed to comorbid migraine in some patients. Methods Patients with a diagnosis of cluster headache from June 2014 to December 2023 were identified from the tertiary headache centre at King's College Hospital, London. Data including age, sex, headache phenotype and headache frequency was collected retrospectively in a cross-sectional design through the use of clinic letters followed by a telephone interview. A Wilcoxon signed-rank test was used to compare number of cluster headache attacks per day pre- and post-verapamil administration. A negative binomial generalized linear model was used to interrogate the relationship between the number of attacks post-verapamil and age, sex, verapamil dosing, comorbid migraine and baseline number of attacks. Results Of 168 patients included, the mean age was 31 years, 73% were male, 46% of patients had chronic cluster headache and 51% had comorbid migraine. During the latest ictal period, the median (interquartile range) frequency of cluster headache attacks per day was 3 (2–5) for the entire sample. The presence of comorbid migraine increased the likelihood of headache exacerbation by verapamil by an odds ratio of 1.616 (95% confidence interval: 1.059–2.465, χ 2 1  = 4.955, P  = 0.026). No differences were observed in the frequency of shadow attacks amongst those with comorbid migraine ( n  = 54/85, 64%) versus patients without migraine ( n  = 48/83, 58%) (Mann-Whitney U  = 3728, z = 0.754, P  = 0.451). No effect was seen on monthly migraine days pre- and post-verapamil administration ( P  = 0.141). Adverse events were reported in 62 of 109 (57%) of patients taking verapamil with the most common being PR interval prolongation (15.6%), lower limb oedema (8.3%), worsened headache (6.4%) and fatigue (6.4%). Conclusions It is likely that the association of cluster headache and migraine is more common than generally thought and co-existence may go under-recognised. Our results show comorbid migraine increased the likelihood of headache exacerbation during the initiation of verapamil. In patients with headache worsening, a dual diagnosis of migraine alongside cluster headache should be considered.